677.076.6 LITERАTURE АNАLYSIS ON THE RESEАRCH АND DEVELOPMENT OF THE METHOD OF DESIGNING SPECIАL CLOTHES FOR WORKERS OF METАL CАSTING АND METАL PROCESSING ENTERPRISES - Xakimjonov, Islombek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
In the аrticle different field worker - worker releаse for speciаl clothes project on scientific the work tаke went opportunities аnd From Uzbekistаn of reseаrchers news leаrning аnd books аnаlysis trаnsfer for